Efficiency of Stem Cell (SC) Differentiation into Insulin-Producing Cells for Treating Diabetes: a Systematic Review - Marzieh Nemati; GolamHossein Ranjbar Omrani; Bahareh Ebrahimi; Aliakbar Alizadeh (Hindawi Limited, 2021)
Over the recent years, the use of stem cells has provided a new opportunity to treat various disorders including diabetes. Stem cells are unspecialized cells with a capacity for self-renewal and differentiation into more specialized cell types. Many factors contribute to the differentiation of SCs and thus play an important role in regulating the fate of stem cells. Accordingly, a wide range of protocols has been used to differentiate SCs to insulin-producing cells but the effectiveness of SC differentiation varies. The aim of this systematic review was to evaluate the results obtained from different studies on SC differentiation for higher efficacy to treat diabetes. This search was done in PubMed, Web of Science (WOS), and Scopus using keywords "insulin-producing cell (IPC)," "pancreatic B cell," "insulin-secreting cell," "stem cell," "progenitor cells," "mother cell," and "colony-forming unit." Among more than 3646 papers, 32 studies were considered eligible for more evaluations. The obtained results indicated that most of the studies were performed on the mesenchymal stem cells (MSCs) derived from different tissues as compared with other types of SCs. Different evaluations of in vitro studies as well as animal models supported their role in the recovery of diabetes. In the present review, we summarize and discuss recent advances in increasing the efficiency of SC differentiation using different materials, but despite the promising results of this systematic review, further studies are needed to assess the efficiency and safety of transplantation of these cells in diabetes recovery.